Trend in prevalence of anemia in children between 6 and 35 months in Peru during the period 2014-2019 - Mougenot, Benoit (2023)
Introduction: In Peru, 4 out of 10 children under 3 years of age suffer from anemia. Objective: to determine the trend in the prevalence of anemia in children aged 6 to 35 months, during the period 2014-2019. The study: We perform a secondary analysis of repeated annual cross sections for the period. We used the chi-square test of joint significance for each category of exposure variables. Findings: The main results show a decrease in the prevalence of childhood anemia during the 2014-2019 period from 46.92% to 40.33%, specifically in girls and boys aged 12 to 24 months. Conclusions: The decrease was greater in rural areas, in the natural regions of Sierra and Selva, among the children of mothers with a higher level of education and households with the highest wealth quintile. The Puno region presents the smallest decrease in childhood anemia during the period analyzed.